Estabelecimento e desenvolvimento inicial de Barueiro (Dipteryx alata vog.) in vitro - Silva, Herick Fernando de Jesus (2015)
The barueiro (Dipteryx alata Vog.) is a fruit crop of the Cerrado of great importance in food and feed, the recovery of degraded areas and landscaping. It is set in an environment where natural devastation promoted by human activities puts you at risk of extinction. Thus aimed to evaluate this work the in vitro establishment of D. alata through the types of culture media used and their modifications. The experiments were conducted in the Biotechnology Laboratory of UFU in Uberlândia- MG. In the first experiment were evaluated three culture, MS, WPM and AA (more water agar), and activated carbon doses (0, 2, 4 and 6 g L-1). After 60 days held the final evaluation. From the results obtained, it was found that the MS medium was more promising for the in vitro establishment of barueiro. As to the coal dose, 3 g L-1 was the positive results favoring development without compromising any structure of the seedlings. In the second experiment were studied concentrations of MS medium (25, 50, 75 and 100%) supplemented with coconut water (100 mL L-1), banana pulp (60 g L-1) and the absence of any organic additive. Through the answers obtained, it was concluded that the supplements used did not promote satisfactory results in the development of the seedlings and the lowest concentration of MS salts (25%) was the favored better results for the in vitro establishment of D. alata. The conclusions reached in these studies were based on the evaluation of the shoot length (CPA), root length (CR), fresh (MF) and dry matter (MSC), stem diameter (DIA), number of leaves (NF) and chlorophyll contents a (CA), B (CB) and total (CT).